Teaching business ethics: Plato was right - David F. Perri; Megan V. Teague (Cogent Business & Management, 2022)
Ethical lapses in major corporations continue to draw public attention to the specter of corporate misconduct. This paper presents a pedagogical approach that is designed to enhance student understanding and appreciation of the challenges that business leaders face when confronted with the conflict between the profit-maximizing demands of capitalism and the ethical expectations of society. This is an approach that fully acknowledges the seductive nature of unethical conduct in search of corporate rewards. This paper presents a method which can be applied both in undergraduate and graduate coursework, facilitates the examination of two corruption cases (Enron and WorldCom), and highlights short-term gain versus the eventual long-term pain of unethical behavior.
Keywords: 650; Business Ethics; Enron; Ethical Decision-Making; Ethics Cases; Pedagogy; WorldCom